Integration of Islamic Values and Science-Technology Ethics in the Formation of Islamic Behavior - Fatima Zulfa; Sinta Sinta; Anggun Desta Maharani; Alihan Satra (SMA Negeri 1 Bangkinang Kota, 2026)
The study purpose was to examine how Islamic values can be integrated with the ethics of science and technology to foster Islamic behavioral attitudes in daily life. Materials and methods. This study uses a library research method. Data were collected from various scientific sources including journals, books, and articles related to the integration of Islamic values in the fields of science and technology. Data analysis was conducted using a descriptive-qualitative approach by elaborating, describing, and synthesizing information from various literature sources. Results. Islamic values—such as tawhid as the foundation of knowledge, honesty, responsibility, and the principle of maslahah—provide a comprehensive moral framework for guiding the development and use of technology. Integration of these values in education and daily life can shape responsible, ethical, and spiritually grounded individuals. Conclusions. The integration of Islamic values with scientific and technological ethics is not merely an academic concern but a necessity for forming a generation that is intellectually capable and morally sound in facing the challenges of the digital era.